Harmoni Pengaturan Surat Ketetapan Penghentian Penyidikan oleh Kepolisian Negara Republik Indonesia. (Lex Journal: Kajian Hukum & Keadilan, 2019)
Starting from the Separation of the National Police of the Republic of Indonesia (Indonesian National Police) and National Tentana Indonesia (TNI), with the Decree of the People's Consultative Assembly of the Republic of Indonesia Number VI / MPR / 2000, and continued with the establishment of Law Number 2 of 2002 concerning the Republic of Indonesia National Police amendment to Law Number. 28 of 1997 and Law Number. 13 of 1961 concerning the National Police of the Republic of Indonesia. In these changes there are legal problems, and need to be studied. By using clear legal theories and concepts, it is hoped that they can find answers to the legal problems of regulating the cessation of investigations by police investigators.Keywords: Harmony of regulation of termination of investigation by the National Police.